(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Embelin, a naturally occurring benzoquinone, is obtained from fruits of Embelia tsjeriam cottam, which plays a vital role in the Ayurvedic system of medicine. An approach for the stress degradation was successfully applied for the development of stability indicating HPTLC method for the determination of Embelin. It was spotted on the plates precoated with silica gel 60 F254 and developed using toluene: ethyl acetate: formic acid, (6:3.5:0.5 v/v/v) as mobile phase. Densitometry analysis was carried out at 291 nm. The method showed high sensitivity with good linearity over the concentration range of 200-1000ng/spot with correlation coefficient value 0.997. The accuracy of the method was established based on the recovery studies. The LOD and LOQ were 6.09ng/band and 18.48ng/band respectively. The system showed a peak for Embelin at Rf of 0.68 ± 0.02.The aim of our study was to observe the effect of various stress conditions on this potential drug candidate. Stress testing of Embelin was carried out according to the International Conference of Harmonization (ICH) guideline Q1A (R2). Embelin was subjected to stress conditions of acid, alkaline hydrolysis, oxidation, photolysis and thermal degradation. A significant degradation was found to occur by acid and oxidation hydrolysis and to a lesser extent under thermal stress and alkaline hydrolysis; and much lesser with photolytic stress. Stress degradation studies on embelin provide an insight into its stability.